Victory at last ; Greening back Mananga ; Small wonder [videorecording] - Lazaro, Cheche (The Probe Team, 1994)
Victims of human rights violations during the Marcos regime who scored victory when a Honolulu court granted them damages; The reforestation of the Mananga mountain in Cebu; Shielu Bharwani's performance on stage becoming popular.